Analisis Kebijakan Provisi Sumber Daya Hutan (PSDH), Dana Reboisasi (DR) Dan Penggantian Nilai Tegakan (PNT) di Provinsi Sulawesi Tengah - Irawan Djamil; Syukur Umar; Golar Golar (Mitra Sains, 2018)
This research aims to know the precision of the benchmark price in calculating PSDH, the precision of rate used for the calculation of PSDH and DR, the precision of PSDH and DR payments through SIMPONI (System Information Non Tax Revenue Online) and to obtain policy recommendations by which the goverment can reallocate the PNT income that were collected in the region of Central Sulawesi Province. Data collection was done by using the questionnaire using Likert Scale measurement methods. By using descriptive analysis, the research results show that : (1) Benchmark prices for group meranti wood and mixed rimba group in calculation of PSDH is lower than respondent’s opinion, while the benchmark prices of wood Indah Group I, Group II and Non-Timber Forest Products (Rattan Batang, Lambang and Tohiti) is not different with that of the respondent’s opinion, (2) use of rates that is used for the calculation of PSDH and DR is not different with that of the respondent’s opinion, (3) Payment of PSDH and DR through Simponi is not different with that of the respondent’s opinion, and (4) Policy recommendation by which the goverment can reallocate the PNT income that were collected is to draw up regulations concerning the return of the PNT to Regions producers because all the provisions regulating the PNT is declared null and void again based on the decision of the Supreme Court of the Republic of Indonesia Number: 12 P/HUM/2015.